Desbaste seletivo de um teste de procedências e progênies de Astronium fraxinifolium e Jacaranda cuspidifolia com base na variação genética de caracteres quantitativos - Cornacini, Maiara Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim is to propose a management plan for progeny and provenance tests of Astronium fraxinifolium Schott and Jacaranda cuspidifolia Mart. It will be based on knowledge of genetic variability in an effort to promote the conservation of their genetic potential for commercial and environmental purposes. The test was originally installed in 1996 in Selvíria, Mato Grossa do Sul (MS) using an experimental design of randomized complete block design. We applied a total of 30 treatments (progenies) of provenance in Ilha Solteira, São Paulo (SP) and 30 treatments of provenance in Selvíria, MS with five repetitions for A. fraxinifolium and 30 treatments and 10 repetitions for J. cuspidifolia. The experimental plots were installed in a linear array, with 10 plants per plot, spaced 3 × 1.5m in alternate plantings. The silvicultural traits of both species were measured from 18 years after planting and sex determination of A. fraxinifolium individuals. The estimates of variance components and genetic parameters were obtained by employing the genetic statistical software SELEGEN-REML / BLUP. To investigate the genetic diversity the Mahalanobis distances and grouping of Tocher optimization model was used. It detected significant differences among provenances for DAP and ALT, between and within progenies for all growth traits, except FOR within progenies in A. fraxinifolium. The heritability coefficient average level progenies ranged from 0.59 to 0.89 and individual heritability from 0.14 to 0.35. The accuracy was high (> 0.65) and the coefficient of genetic variations were higher than 5.6. From total number of A. fraxinifolium individuals of just 11% and 16% are in flowering from Ilha Solteira, SP and Selvíra, MS provenances, respectively; with a predominance of individuals with male flowers. The Mahaloanobis distance was found at a maximum distance of 31.75 and a low of 0.23 between progenies. The A. fraxinifolium progenies of Ilha Solteira and Selvíria were grouped into eight and four groups. J. cuspidifolia progenies were grouped into six groups. The selection strategy within progenies, with selection of 50% of individuals based on DAP trait, revealed low gains in the selection. However, it is more suitable for this test because it does not alter the genetic structure of the population nor does it reduce the likelihood of crossings between relatives. Therefore, this proposal for selective thinning is most appropriate as the flowering percentage of individuals is low, making it impractical sex determination of total individuals. Consequently, the estimates of the parameters accurately suggest such an application is at a high level of selective high intensity.

O objetivo do trabalho foi propor um desbaste seletivo visando o manejo de um teste de progênies e procedências de Astronium fraxinifolium Schott e Jacaranda cuspidifolia Mart com base no conhecimento da variabilidade genética, visando a conservação do seu potencial genético para fins comercial e ambiental. O teste foi instalado em 1996 em Selvíria-MS, sendo o delineamento experimental utilizado de blocos completos casualizados. Foram utilizados 60 tratamentos (progênies) sendo 30 da procedência de Ilha Solteira-SP e 30 da de Selvíria-MS com cinco repetições para A. fraxinifolium e 30 tratamentos e 10 repetições para J. cuspidifolia. As parcelas do experimento foram instaladas, obedecendo a uma disposição linear, com 10 plantas por parcela, no espaçamento de 3 × 1,5 m, em plantio alternado. Foram mensurados os caracteres silviculturais das duas espécies aos 18 anos após o plantio e a sexagem dos indivíduos de A. fraxinifolium. As estimativas de componentes de variância e parâmetros genéticos foram obtidas empregando-se o software genético-estatístico SELEGEN-REML/BLUP. Para investigar a divergência genética utilizou-se as distâncias de Mahalanobis e o agrupamento por otimização de Tocher. Detectou-se diferenças significativas entre procedências para os caracteres DAP (diâmetro a altura do peito) e ALT (altura total da planta), entre e dentro de progênies para todos os caracteres de crescimento, exceto FOR (forma de fuste) dentro de progênies em A. fraxinifolium. O coeficiente de herdabilidade em nível de média de progênies variou de 0,59 a 0,89 e a herdabilidade individual de 0,14 a 0,35. A acurácia foi alta (> 0,65) e os coeficientes de variação genética foram maiores que 5,6. A porcentagem de indivíduos em floração nas procedências de Ilha Solteira e Selvíria de A. fraxinifolium foram de 11% e 16%, respectivamente, com predominância de indivíduos com flores masculinas. As progênies de A. fraxinifolium de Ilha Solteira e Selvíria foram agrupadas em oito e quatro grupos e as progênies de J. cuspidifolia em seis grupos pela otimização de Tocher. A estratégia de seleção dentro de progênies, com seleção de 50% dos indivíduos com base no caráter DAP, revelou baixos ganhos na seleção, porém é a mais indicada para esse teste, pois não alterará a variabilidade genética da população e diminuirá a probabilidade de cruzamentos entre parentes. Essa proposta de desbaste seletivo é mais adequada visto que a porcentagem de indivíduos em florescimento é baixa, o que inviabiliza a sexagem completa do teste, e, consequentemente, as estimativas mais acuradas de parâmetros genéticos como o tamanho efetivo populacional.
Selective thinning in a provenances and progenies test of Astronium fraxinifolium and Jacaranda cuspidifolia based on genetic variation of quantitative traits
Keywords: Conservação genética; Espécies nativas; Manejo florestal; Gonçalo alves; Jacarandá caroba; Genetic conservation; Native species; Forest management